Solving combinatorial optimization problems by soft computing - Li, Sa. (2008)
This thesis is concerned with a novel algorithm, generalized from Chaotic Simulated Annealing (CSA) by adding a decreasing random noise into the neuron inputs in CSA to combine the best feature of both stochastic simulated annealing (SSA) and CSA, i.e., stochastic chaotic simulated annealing (SCSA).